Scrutinizing Creative Economic Development at Cimahi Technopark: An Agile Governance Perspective - Nur, Mohamad Ichsana; Alpin, Alpin; Rohimat, Muhammad Febriansyah; Lutpi, Supi Ainul (KnE Social Sciences, 2022)
The shift in economic orientation from manufacturing to a creative economy provides new potential for improving the national economy. Indonesia has the opportunity and potential to develop a creative economy, particularly given its cultural diversity and abundance of human resources. In order to seize these opportunities, the City Government of Cimahi created the Cimahi Technopark through Perwal No.14 of 2018 concerning Cimahi Technopark as a Science and Technology Area, in the context of utilizing human resources to provide solutions for the limited availability of natural resources. The research objective was to analyze the implementation of agile governance at Cimahi Technopark in developing the creative economy. This was descriptive research utilizing qualitative methods. Data were collected using structured interviews, a literature review and unstructured observations in the research location. The results showed that Cimahi Technopark reflected the concept of agile government, even though there were some deficiencies in its implementation. Keywords: agile governance, local government, creative economy, citizen empowerment, Cimahi Technopark